PENERAPAN DATA MINING PADA PENJUALAN PRODUK ELEKTRONIK - Primadona, Primadona; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2023)
Surya Jaya Electronic & Furniture, the author found many obstacles due to the accumulation of annual sales data. This made it difficult for the company to know the availability of existing goods and could not predict which goods or products were most in demand by customers and sold the most. Implementation of data mining with the a priori algorithm on Surya Jaya Electronic & Furniture found that in June there were 23 data points for item set 2, 8 data points for item set 3, and 35 data points for item set 4. In the July period, there were 19 data points for item set 2, 13 data points for item set 3, and 33 data points for item set 4, and in the August period, there were 15 data points for item set 2, 1 data point for item set 3, and 7 data points for item set 4.